A comparative study on disqualification of company directors in the UK and Nigeria: lessons for Turkey. Issue 2 (11th March 2020) - Caliskan, Samet; Subai, Pereowei
Abstract : Purpose: The purpose of this paper is to argue that the disqualification of directors, coupled with other liabilities to which they may be subjected, particularly in insolvency, should be sufficient to deter wrongdoing, because of the impact they tend to have on their personal and professional lives. It, however, argues that the "deterrence" effect would be dependent on the existence of other factors such as the efficient application of the law, publicity and post-disqualification monitoring. Design/methodology/approach: Using the UK as its primary case study, while also making reference to Nigeria and Turkey, this paper will show that while the existence of disqualification as a sanction exists in the first two countries, it is virtually absent from Turkey. And that while directors' disqualification provisions are routinely applied in the UK, they are hardly invoked in Nigeria, except perhaps with respect to listed companies, due perhaps to a lack of awareness of its existence or potency. Findings: This paper will conclude by making a case for a stronger application of the law, as it relates to directors' disqualification in the UK, call for an elaboration of the legal framework in Nigeria as well as the need for a public awareness of its provisions and potential impact and contend that Turkey should put in place a legal framework for directors' disqualification patterned also after the UK framework. Originality/value: The uniqueness of this paper stems from its tri-country focus. In that respect, the UK, which is a more advanced economy, with a robust and dynamic company law regime, is used as the primary case study, whereas at the same time, developments in Nigeria, particularly with that country's capital market, will be extracted and compared with the UK framework. Turkey, on the contrary, has been chosen as a case study mainly because it has no directors' disqualification mechanism in its legal system. Comparing directors' disqualification in one developing country, Nigeria, and a developed country, the UK and determining their upsides and downsides will be beneficial to Turkey in respect to establishing a deterrent effective disqualification mechanism on directors.